Grandma's shoes - Hathorn, Elizabeth; Savadier, Elivia (Boston : Little, Brown, 1994)
A young girl copes with her grandmother's death with the help of the old woman's shoes and some special memories.
School Library Journal
4.5
K-3
Keywords: Grandmothers -- Fiction; Death -- Fiction; Grandmothers -- Fiction; Death -- Fiction